Correlation between physico-chemical water quality and river ecosystems in Malaysia rivers with different land uses. Issue 1 (August 2021) - Aweng, E R; Sharifah Aisyah, S O; Salam, M A; Mior, I B
Abstract: River water quality is one of the major issues in water supply in Malaysia. Most people understand that, water pollution caused by the discharge from the factories and municipal waste but is that the real case? So, in order to answer the above question, this study was done to determine the interaction or correlation between physico-chemical water quality and river ecosystems. Component of river ecosystems measured are river riparian composition, large woody debris (LWD), canopy cover and substrate composition (D50). This study was conducted in Sungai Mengkibol, Sungai Madek and Sungai Dengar in Johor. There were a total of five sampling sites, three for impact stations and two as reference stations, including one highland station. For water quality, six in-situ parameters were measured namely temperature, conductivity, dissolved oxygen (DO), pH, turbidity and salinity using a multi parameter probe as well as a single parameter probe. Meanwhile, field survey form was used to assess river habitat namely river riparian compositions, canopy cover and LWD. In addition, Pebble Count Method was used to measure substrate compositions (D50). Results shows that, physico-chemical water quality was correlated ( p < 0.05) with riparian cover, LWD and canopy cover but it was not correlated ( p >0.05) with substrate composition (D50) of the river. Based on the results obtained from the study, it can be suggested that physico-chemical river water quality was not caused by pollution alone but river ecosystems were also played significance role in determining the quality of water. Hopefully, this finding can be used by the responsible authorities for effective river management in order to sustain our drinking water supply.